Long-Term Trends in Esophageal Candidiasis Prevalence and Associated Risk Factors with or without HIV Infection: Lessons from an Endoscopic Study of 80,219 Patients - Takahashi, Yuta (PLoS One, 2015)
BACKGROUND: The prevalence of candida esophagitis (CE) might be changing in an era of highly active antiretroviral therapy (HAART) among HIV-infected patients or today’s rapidly aging society among non-HIV-infected patients. However, few studies have investigated long-term CE trends, and CE risk factors have not been studied in a large sample, case-control study. This study aimed to determine long-term trends in CE prevalence and associated risk factors for patients with or without HIV infection. METHODS: Trends in CE prevalence were explored in a cohort of 80,219 patients who underwent endoscopy between 2002 and 2014. Risks for CE were examined among a subcohort of 6,011 patients. In risk analysis, we assessed lifestyles, infections, co-morbidities, immunosuppressants, and proton-pump inhibitors (PPIs). All patients were tested for HIV, hepatitis B or C virus, and syphilis infection. For HIV-infected patients, sexual behavior, CD4 cell count, history of HAART were also assessed. RESULTS: CE prevalence was 1.7% (1,375/80,219) in all patients, 9.8% (156/1,595) in HIV-infected patients, and 1.6% (1,219/78,624) in non-HIV-infected patients. CE prevalence from 2002-2003 to 2012-2014 tended to increase in non-HIV-infected patients (0.6% to 2.5%; P<0.01) and decrease in HIV-infected patients (13.6% to 9.0%; P=0.097). Multivariate analysis revealed increasing age (odds ratio [OR], 1.02; p=0.007), HIV infection (OR, 4.92; p<0.001), and corticosteroid use (OR, 5.90; p<0.001) were significantly associated with CE, and smoking (OR, 1.32; p=0.085) and acetaminophen use (OR, 1.70; p=0.097) were marginally associated. No significant association was found with alcohol consumption, hepatitis B or C virus, syphilis, diabetes mellitus, cardiovascular disease, cerebrovascular disease, chronic kidney disease, liver cirrhosis, anticancer, or PPIs use. In HIV-infected patients, CD4 cell count <100/μL (OR, 4.83; p<0.001) and prior HAART (OR, 0.35; p=0.006) were independently associated with CE, but sexual behavior was not. Among corticosteroid users, CE was significantly associated with higher prednisone-equivalent dose (p=0.043 for trend test). CONCLUSIONS: This large, endoscopy-based study demonstrated that CE prevalence increased in non-HIV-infected patients but decreased in HIV-infected patients over 13 years. Risk analysis revealed that increasing age, HIV infection, and corticosteroids use, particularly at higher doses, were independently associated with CE, but alcohol, other infections, diabetes, anticancer drugs, and PPIs use were not.